A New Antiarrhythmic Drug in the Treatment of Recent‐Onset Atrial Fibrillation: Vernakalant. Issue 5 (12th September 2013) - Vizzardi, Enrico; Salghetti, Francesca; Bonadei, Ivano; Gelsomino, Sandro; Lorusso, Roberto; D'Aloia, Antonio; Curnis, Antonio
Summary: Vernakalant is a new antiarrhythmic agent recently approved in Europe for the rapid cardioversion of recent‐onset atrial fibrillation. It works by blocking early‐activating K+ atrial channels and frequency‐dependent atrial Na+ channels, prolonging atrial refractory periods and rate‐dependent slowing atrial conduction, without promoting ventricular arrhythmia. Preclinical and clinical trials showed good toleration of this drug. The main purpose of our review is to describe all the trials that led to the incorporation of vernakalant into the current European atrial fibrillation guidelines.